Narrativas jornalísticas sobre mulheres envolvidas no tráfico de drogas no estado do Pará e do Amazonas - Rosa, Ana Cleia Ferreira (2023)
This dissertation seeks to analyze journalistic narratives about women involved in drug trafficking to observe how the crime is reported, which sources are heard and what is the profile of women involved in these crimes. The methodology used to develop the research was content analysis and journalistic narrative analysis. In order to understand the construction of journalistic narratives of drug trafficking crimes in which women are involved, news published in the newspapers O Liberal do Estado do Pará and A Crítica do Estado do Amazonas in 2018 were collected. of women in drug trafficking in the journalistic narratives analyzed happened as a result of their condition of social vulnerability and affective relationships. In addition, the research highlighted that journalism as a social actor that contributes to the socialization of people needs to expand the space of narratives for social problems that widely affect men and women in society, as is the case of drug trafficking.